Incidence of Acute Renal Failure in Full Term Neonates with Birth Asphyxia - Jha, Chandra Bhushan; Tamrakar, Akhil (Birat Journal of Health Sciences, 2019)
Introduction: Birth asphyxia is an eventuality having far reaching consequences in the neonatal period. Hypoxia and ischemia can cause damage to almost every tissue and organ in the body and various target organs involved. Renal insult is a recognized complication of birth asphyxia and carries a poor prognosis. Timely detection of renal dysfunction and appropriate management may favorably alter the prognosis in many neonates with birth asphyxia. Objective: The present study was done to find out the incidence of acute renal failure in the full term neonates with birth asphyxia. Methodology: A cross sectional study was conducted at Birat Medical College Teaching Hospital, Morang, Nepal from 1st September 2017 to 28th February 2018. Fifty full term neonates born with Apgar score of <6 at 5 minutes and fulfilling inclusion criteria were enrolled in the study. Asphyxiated neonates having Serum creatinine >1.5gm/dl or urine output<1ml/kg/hr were labeled as cases of Acute Renal Failure. Blood sample for serum creatinine was collected at 24hrs, 48 hrs and 72 hrs of life. Results A total of 50 term asphyxiated neonates were enrolled in the present study. Among them 54% and 46% were males and females respectively with male to female ratio of 1.2:1. In the present study 62% of cases developed acute renal failure in either of the first three days of life with mean urine output 1.02±0.27ml/kg/hr and mean serum creatinine of 1.49±0.32 mg/dL. The incidence of oliguric renal failure was 52% and non oliguric renal failure was 48%.The association between serum creatinine and urine output was statistically significant. Conclusion: In the present study birth asphyxia has been an important cause of neonatal acute renal injury, revealing 31 (62%) cases. Monitoring urine output and serum creatinine has helped in detecting the asphyxiated neonates with acute renal injury in the early stage.